Pembelajaran Jarak Jauh Maasa Pandemik - Ratih Bayuningsih; Siti Syakira Hamdi; Casman (Akademi Keperawatan Hermina Manggala Husada, 2022)
In the teacher's point of view that the implementation of PJJ is considered less effective due to some teachers being unable to understand the use of technology, and the ability and level of student motivation is low, even teachers have difficulty monitoring students, teachers have difficulty evaluating students, students do not participate actively, students are not conducive (doing other things outside of what they should be), teacher and student interactions are not developed, student learning competencies are not achieved, learning outcomes are not optimal, learning materials are not delivered, families are less involved and have limitations in supporting student learning facilities. And on the other hand, the reason teachers think that PJJ can be done effectively is if teachers can use technology in learning, teachers can manage time, students have independent characteristics, teachers can convey material clearly and interestingly, students can participate actively, students do the assignments and exams given, teachers can build interaction between parents and students, test scores are achieved, learning materials are delivered to the maximum, families participate and facilities that support student learning.